Highly Efficient Kinetic Resolution of Aryl-Alkenyl Alcohols by Ru-Catalyzed Hydrogen Transfer - Yipeng You; Ming Yu Jin; Guanyu Tao; Xiangyou Xing (Molecules, 2021)
No matter through asymmetric reduction of ketones or kinetic resolution of secondary alcohols, enantioselective synthesis of the corresponding secondary alcohols is challenging when the two groups attached to the prochiral or chiral centers are spatially or electronically similar. For examples, dialkyl (sp3 vs. sp3), diaryl (sp2 vs. sp2), and aryl-alkenyl (sp2 vs. sp2) alcohols are difficult to produce with high enantioselectivities. By exploiting our recently developed Ru-catalysts of minimal stereogenicity, we reported herein a highly efficient kinetic resolution of aryl-alkenyl alcohols through hydrogen transfer. This method enabled such versatile chiral building blocks for organic synthesis as allylic alcohols, to be readily accessed with excellent enantiomeric excesses at practically useful conversions.